Pengembangan E-Modul Berbasi Model Pembelajaran Inquiry Terhadap Kemampuan Berpikir Kritis Dalam Materi Pola Bilangan - Lidi Wina Domina; Yudi Darma; Yadi Ardiawan (Universitas Muhammadiyah Semarang, 2024)
This research aims to produce an e-module based on an inquiry learning model to improve students' critical thinking skills in number pattern material for class VIII SMP Negeri 13 Pontianak by achieving levels of validity, practicality and effectiveness. This research method applies Research and Development involving 3 material validator experts and 3 media expert validators. The subjects of this research were 24 students in class VIII of SMP Negeri 13 Pontianak. Data collected were validation sheets, teacher response questionnaires, student response questionnaires, interviews and students' critical thinking ability tests. The results of this research show that the e-module validity assessment is at 84.1% (Quite Valid) criteria, the practicality assessment is at 89.1% (Very Practical) and the effectiveness assessment is at 70.8% (Effective). So it can be stated that the e-module is suitable for use as a learning medium for class VIII SMP Negeri 13 Pontianak regarding the subject of number pattern systems.